Body image in children and adolescents diagnosed with the human immunodeficiency virus: a systematic review - Silva, Diego Augusto Santos; Silva, Andressa Ferreira da; Zanlorenci, Suellem (São Paulo Medical Journal, 2023)
CONTEXT: The relationship with body image, which is the way the body presents itself to each subject, can be aggravated in children and adolescents diagnosed with an human immunodeficiency virus (HIV) infection, since these patients use antiretroviral therapy and may suffer from the adverse effects of the treatment due to continuous use of medication. OBJECTIVE: To estimate the prevalence of body image dissatisfaction, to describe the assessment methods, and to identify associated factors in children and adolescents diagnosed with HIV. DESIGN AND SETTING: This is a systematic review. Department of Physical Education, Florianópolis - Brazil METHODS: We followed the procedures of the Preferred Reporting Items for Systematic Reviews (PRISMA) and the Cochrane recommendations in the selection of articles through a search performed in eight databases. RESULTS: Prevalence of body image dissatisfaction due to thinness was between 36.7–52.0% in males and 28.1–36.4% in females, and body image dissatisfaction due to overweight was between 8.0–31.2% in males and 21.9–50.0% in females. Factors associated with body image dissatisfaction were as follows: female sex, older age, low levels of physical activity, low self-esteem, higher body fat, higher body weight, greater arm muscle area, triceps skinfold thickness, and higher body mass index. CONCLUSION: Children and adolescents of both sexes diagnosed with HIV infection are dissatisfied by thinness and overweight of their body image. REGISTRATION: https://www.crd.york.ac.uk/prospero/ (CRD42021257676).